Pegadas de dinossáurios no Geocircuito de Sesimbra - Santos, V. F. (2018)
In Portugal since the XVth century, or even earlier, people from the Sesimbra region looked at and interpreted the dinosaur footprints on the cliffs of Cabo Espichel as having been produced by a “giant mule” that carried the Virgin Mary from the stormy sea to safety at the top of the cliffs. This became a religious myth and gave origin to the construction of the Cabo Espichel Sanctuary during the XVIIIth century. Centuries later these footprints were finally recognized as what they indeed are: Upper Jurassic sauropod footprints. Over the last 50 years fieldwork in the region has allowed the recognition of several levels with dinosaur trackways between Cabo Espichel and Lagosteiros bay and in the area of Zambujal. At present, there are five dinosaur tracksites in Portugal designated as Natural Monuments, three of them in the Sesimbra area. Besides their scientific interest, they play an important role to enhance public awareness of geological heritage and, consequently, it will be possible to attain more success on geoconservation strategies in order to protect and to value the geological and palaeontological heritage. These geosites are an important and well known component of the Sesimbra GEOcircuit that aims to catalogue, to characterize, to interpret and to promote the geological heritage of Sesimbra.